A controlled process of atomic-scale material design via temperaturemediated grain refinement of NiCo2O4 rods for capacitive energy storage - Padya, Balaji (H. : ĐHQGHN, 2020)
We report on a controlled process of atomic-scale material design based on calcination-temperatureinduced structural variation and its influence on capacitive energy storage characteristics of spinelstructured NiCo2O4 rods (NCOR). Precisely, morphology-tuned NCOR were grown through a facile solvothermal process followed by a controlled calcination. The meticulous thermal-kinetics study revealed that the activation energy of 269.53 kJ/mol could transform the hydroxides into oxides completely. The precipitate was annealed at variable temperatures (350, 450 and 550 C) to incorporate structural changes with variation in size of the crystallites. NCOR-450 consisting of fine-sized nanocrystallites coated on a flexible graphite foil exhibited a maximum gravimetric specific capacitance of 326.1 F/g at a constant current density of 0.5 A/g. The comparatively smaller crystallites lead to attractive capacitances as the temperature-induced grain-growth-correlated electrical properties influence the electrochemical properties significantly.